Overview on Mechanisms and Complications of Dental Bleaching: Life Sciences-Medicine - Siddik Noorsaeed, Dr Ashwag; Ali A Alkhatti, Eman; Nuwaymi M Aletayani, Hatun; Mansor S Alamer, Sondus; Zaid M Alsamari, Alhanouf; Mohammed J Alwuhaimed, Sarah; Abdullah S Almoshaddak, Reem; Eid W Alqarafi, Faris; Abdullah Batarfi, Amal; Khalid Alzahrani, Nada; Adnan Alghuneem, Reem; Saadallah A Alsulami, Fahad; et al. (International Journal of Life Science and Pharma Research, 2022)
Abstract: The practice of bleaching teeth is very common, and various tools and methods have been developed specifically for this purpose. Whiten teeth, various approaches and products are available, each with a distinctive mode of operation. These include products used at home, such as toothpaste, gels, and films, and systems used in dental offices where products with highly concentrated bleaching agents are used under close supervision. Intrinsic and extrinsic staining are the two main types of tooth discolouration causes. Intrinsic staining, also known as internal staining, can be caused by a variety of things, including genetics, ageing, antibiotics, high fluoride levels, and developmental disorders. It can even begin before the tooth has fully emerged. The effectiveness of these various techniques depends on the specific tooth discolouration being treated. Dental bleaching procedures have emerged due to technical advancements to make the procedure easier to use and increase comfort, safety, and efficiency. External dental whitening is typically accomplished with hydrogen peroxide that has been photoactivated or not or carbamate. However, the teeth whitening process in the home and business leads to sensitivity. Certain risks associated with tooth whitenings, such as increased tooth sensitivity and gingival irritation, have been known to the public and professional communities. Recent research has identified other risks, including tooth surface softening and roughening, increased demineralization risk, dental restoration degradation, and unfavourable colour change. This article aims to review and synthesize the most recent research on tooth bleaching methods and side effects.